The Effect of the Make a Match Learning Model on Mathematics Learning Outcomes of Harapan Mekar Medan Private Middle School Students - Herfina, Yunia; Ammy, Putri Maisyarah (Lembaga Riset Mutiara Akbar, 2023)
The formulation of the problems in this study are: (1) is there any effect of the Make a Match model on the mathematics learning outcomes of SMP Harapan Mekar Medan students. (2) what percentage of the influence of the Make a Match learning model on the mathematics learning outcomes of SMP Harapan Mekar Medan students. The aims of this study were: (1) to determine the effect of using the Make a Match learning model on the mathematics learning outcomes of Harapan Private Middle School students. (2) to find out what percentage of the influence of the make a match model on student learning outcomes at SMP Harapan Mekar Medan. The population and sample in this study were students of the Experiment class as class VII A and the control class as class VII B at Harapan Mekar Middle School Medan, totaling 20 people, the Experiment class where there were 13 male students and 7 female students and the Control class totaling 20 people. with 7 male students and 13 female students. This type of research is experimental research with a research design using two classes. The research instrument uses an essay test about the set. The data collection technique used an initial test (pretest) and a final test (posttest). Technical data analysis using the normality test. Hypothesis testing was used for the t test and determinant test and the results of the study used an unpaired sample t-test using SPSS 22 which produced a significance of 0.000 <0.05, so it was proven that H_1 was accepted H_0 was rejected. And the results of the determinant test carried out were obtained at 36.23%. So, it can be concluded that the influence of the Make a Match learning model on the mathematics learning outcomes of SMP Harapan Mekar Medan students is 4.877%.